TRANSLATION OF COMPARATIVE MEANS EXPRESSING PERSONALITY AND CHARACTER RELATIONSHIP IN “BABURNAME” (Scientific journal of the Fergana State University, 2023)
This article is considered an exemplary work “Baburname” that shows the role of the author in history, his unique service, the way of struggle, skill and perseverance, and his central character is certainly Mirza Babur, who developed a method of depiction unique to “Baburname”, which he presents with great skill. In Babur's method of comparison, all events, persons, their comparative images revolve around an "axis" and are dedicated to their adequate translation in translations